M. I. KALKO: POLY-SEMANTIC VERB AS AN OBJECT OF MODELING THE ASPECTUAL PARADIGM - KALKO, M. I. (Linguistic Bulletin (Movoznavchyi Visnyk), 2021)
Summary. Introduction. Analyzing the Ukrainian language aspect studies reveals a spectrum of investigation perspectives. One of them is distinguished in the complex approach to the category of aspect as a dynamic and integrated multi facet phenomenon. It fully determines investigating the aspect grammar not solely but in lieu with other components of the aspect theory, mainly with aspect classes. Purpose. Through all this, the article is aimed at applying the objectivist approach to describing the verbal aspect that enables, with the appropriate research instrumental means, to create a real and detailed, though not schematic, aspectual «picture» of a poly-semantic verbal lexeme. Methods. Complex aspectual diagnostics as integrating methods that presume motivated application of logical, component, word-building, oppositional and distributive analyses, selection of native correlative discourse samples etc. Results. The article, through a modern Ukrainian poly-semantic verb, clearly regards the perspective of employing the objective means for describing categories of aspect and aspectuality. The paper supports that the approach enables, through appropriate investigatory means (i. e. complex aspectology survey), to create objective and detailed but no simplified, schematic model for the aspectual paradigm in poly-semantic verbal lexeme. Originality. Aspectual macro paradigm is constituted by: 1) aspectual lexical micro paradigm consisting of aspectual lexical classes: terminative, activitive, stative, eventive, relative; 2) aspectual grammatical micro paradigm, with aspectual grammatical classes: imperfectives-partners, perfectives-partners, imperfektiva tantum, perfektiva tantum, biaspectives; 3) aspectual pragmatic micro paradigm integrating concrete aspect functions, among them progressive, iterative, preasens historicum, concrete factual, etc.; 4) aspectual derivatological micro paradigm consolidating actional subclasses (traditional genders, or moods), like morphologic word-building prefixal, suffixal, confixal derivatives: atenuatives, distributives, duratives, perduratives, saturatives, semelfactives, cumulatives, reduplicatives, etc. Conclusions. Objective approach to investigating the verbal aspect perspectives, focused on the opposed grammar and lexical features, is certain to involve the necessity for the detailed research of the relations between the aspect category and the context. This is theappeals for further linguistic investigation of grammar and vocabulary interaction in the research for the Ukrainian verb aspect.